Importance of carbon source feeding and pH control strategies for maximum kojic acid production from sago starch by Aspergillus flavus - Rosfarizan, Mohamad; Arbakariya, Ariff; Hassan, Mohd Ali; Abdul Karim, Mohamed Ismail; Hiroshi, Shimizu; Suteaki, Shioya (Elsevier, 2002)
To maximize kojic acid production by Aspergillus flavus Link 44-1 using gelatinized sago starch as a carbon source, the performance of different fermentation modes (batch and fed-batch with different feeding modes) was investigated in an 8-l stirred tank fermentor. The addition of a large volume of concentrated sago starch (140 g/l) 2 d after the start with an initial starch concentration of 60 g/l produced the maximum concentration of kojic acid (16.43 g/l), which was about 4 times higher than that for batch fermentation of 100 g/l sago starch. Further improvement of kojic acid production was obtained by adding small amounts of concentrated starch (140 g/l) intermittently at 2-d intervals to the culture. Using this technique of fermentation, the dissolved oxygen tension (DOT) can be controlled at high levels (40-50% saturation) during the active growth phase, which is required for the enhanced secretion of α-amylase used for saccharification of starch and also for the production of mycelia with higher ability in synthesizing kojic acid. Maintaining the culture pH at 3 throughout the intermittent fed-batch fermentation reduced kojic acid production (7.26 g/l) significantly. Very little kojic acid (0.93 g/l) was produced when the pH was kept at 4 during the growth phase and then lowered to 3 during the production phase. A high level of kojic acid production (31.00 g/l) was achieved in fermentation where the pH was not controlled throughout the cultivation or not controlled during the growth phase but kept at 3 during the production phase. This result indicates that the pH control strategy is important; with the variation in culture pH during the growth phase being most significant and critical to kojic acid production.